Draw yourself: How culture influences drawings by children between the ages of two and fifteen - Restoy, Sophie; Martinet, Lison; Sueur, Cédric; Pelé, Marie (Frontiers in Psychology, 2022)
The place children live strongly influence how they develop their behaviour, this is also true for pictorial expression. This study is based on 958 self-portraits drawn by children aged 2-15 years old from 35 countries across 5 continents. A total of 13 variables were extracted of each drawing allowing us to investigate the differences of individuals and environment representations in these drawings. We used a principal component analysis to understand how drawing characteristics can be combined in pictorial concepts. We analysed the effect of age, gender, socioeconomic and cultural factors in terms of complexity and inclusion of social (human figures) and physical (element from Nature and man-made elements) environments, their frequencies, size and proportions of these elements on each drawing. Our results confirm the existence of cultural variations and the influence of age on self-portrait patterns. We also observed an influence of physical and socio-cultural contexts through the level of urbanization and the degree of individualism of the countries, which have affected the complexity, content and representation of human figures in the drawings studied.